Meningkatkan Peran TPQ An-Nur Desa Bekiring Dalam Mengajarkan Tajwid - Nofitasari, Dewi; Susanto, Hanafi Hadi (Social Science Academic, 2025)
This research was motivated by the importance of studying tajweed. And also because it is motivated by the importance of understanding the material tajwid science because The law of reading the Qur'an with tajwid is fardhu 'ain, especially for future tahfidz students. This research is intended to answer these problems. The purpose of this learning is to improve the child's ability to read the Al-Qur'an properly and correctly. Knowledge of the study of the Qur'an is useful for believing and practicing the teachings of his religion so that children become someone who has a Muslim personality. The method used is the ABCD (Asset Based Community Development) approach by emphasizing empowerment, understanding the potential and challenges that are owned to improve the quality of individuals and groups. Based on the ABCD Method, the activity begins with conducting research or observing conditions in the field, the authors find that one of the problems in TPQ An-Nur Krajan Hamlet Bekiring Village is still lacking in the application of learning. This is due to the lack of teaching staff, namely there is only one teacher who does not mention the science of repitation in his lesson. It was from here that the KPM team saw potential with the hope of developing and looking for additional teaching staff who could help teach Mr. Kyai Jemangin as a teacher at TPQ An-Nur Bekiring Village.